The Influenceof Cooperative Learning Model Group Investigation (GI) Type and Learning Motivation Approach With the Understanding Concepts and Solving Mathematical Problem on Grade 7 in Upt Smp Negeri Airpura - Erna Butsila Wati; Ahmad Fauzan (International Journal of Educational Dynamics, 2020)
The aims from this study observe at the influenceof cooperative learning model group investigation (GI) type and learning motivation on students' ability to understand concepts and solve problems in Mathematics in UPT SMP Negeri Airpura both to the students who had high previous knowledge and those who had low previous knowledge.This was a quasi experimental research. Samples are choose using randomized sample. Data are analyzed using t-test, Mann Whitney test and two Ways Anova using MINITAB software. The result of data analysis showed that : (1) the influenceof cooperative learning model group investigation (GI) type and learning motivation can improve students' MGI skills and still need to improve their ability to understand concepts., (4) there was no interaction between learning approaches and previous knowledge toward the eighth grade students.